Education in the Social Context - Kostić, Tatjana (Sociološki pregled, 2020)
Education and textbooks are always connected with the social context. The social context that has influenced education and textbooks in Serbia ever since the end of the World War Two is based on the socialist and post-socialist cultural pattern. The informatics society has inevitably affected culture and education. The work analyzes the changes that have led to the modifications in education and textbooks. The result is that education and textbooks suffer the influences of the society, but that the society also suffers their influence. The conclusion is that without raising the level of education Serbian culture and the society embodied in it cannot be preserved and there can be no social progress; the most efficient way of attaining improvement is to create textbooks which, regardless of frequent changes in cultural patterns, must be guardians of the patterns of culture.